Peran Orang Tua dalam Meningkatkan Pendidikan Karakter Anak Usia Dini pada Aktivitas Pembelajaran di SDN 55/1 Sridadi - Diah Pertiwi; Marihani Desnawati Sipayung; Syahrial Syahrial; Silvina Noviyanti (AS-SABIQUN, 2022)
This study aims to examine the role of parents in improving early childhood character education in learning activities at SDN 55/1 Sridadi. This research method uses a qualitative case study approach. The data collection technique used an interview with the homeroom teacher of class V. Observations in class V at SDN 55/1 Sridadi and study of documentation such as diaries, and work documented in the classroom. Technical analysis of data by selecting the data that is needed and discarding data that is not needed, then it is presented in a complete and well explained, and concluded and verified the data. The results of this study indicate the role of parents in improving children's character education through learning strategies and methods. At SDN 55/1 Sridadi together with parents and teachers must work together and communicate with each other through diaries or meet directly regarding child development.